Implications of Institutional Vacuum in Wetland Conservation for Water Management. (January 2016) - Bassi, Nitin
Wetlands are distinct ecological systems which provide numerous ecosystem services to human society and the environment. However, many of these important ecologically sensitive systems are threatened or are already lost, mainly due to anthropogenic pressures and land-use changes in their catchments. This article looks at the status of wetlands in India, discusses the existing legal and policy framework for wetland conservation, identifies the institutional vacuum leading to the loss of these freshwater ecosystems and assesses their implications for water management. The analysis indicates that it is difficult to estimate any sequential change in the overall wetland area by using estimates available from various wetland inventories since they all have used different methodologies and have considered different types of wetlands in their assessments. Further, deficient policy framework, poor implementation of existing policies and lack of interdisciplinary approach are the major institutional inadequacies in the approach to wetland conservation in India. As a result, various water management functions performed by wetlands, such as freshwater supplies, flood control, groundwater recharge and wastewater treatment, are under immense threat. Regulation of land-use changes in the catchment areas, pollution prevention and periodic assessment of water quality are suggested as major strategies to maintain the hydrological and ecological integrity of wetlands.